2005
DOI: 10.1007/s10384-004-0169-5
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between peripheral anterior chamber depth evaluation using the van Herick technique and angle width evaluation using the Shaffer system in Japanese

Abstract: The van Herick technique closely coincided with the Shaffer system and was found to have a potential for use as a simple method for evaluating narrow-angle eyes in Japanese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 6 publications
1
12
1
Order By: Relevance
“…Studies have shown good performance of limbal anterior chamber grading for detecting occludable angles. [20][21][22][23] The Pentacam rotating Scheimpflug camera is useful for screening patients because important parameters, especially chamber angle in different positions, ACD, pachymetry, corneal radii and diameter, and lens position, can be evaluated in 1 examination within a very short period with good reliability. Our results suggest that central ACD only slightly indicates the potential risk for the development angle-closure glaucoma because a great range of variation was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown good performance of limbal anterior chamber grading for detecting occludable angles. [20][21][22][23] The Pentacam rotating Scheimpflug camera is useful for screening patients because important parameters, especially chamber angle in different positions, ACD, pachymetry, corneal radii and diameter, and lens position, can be evaluated in 1 examination within a very short period with good reliability. Our results suggest that central ACD only slightly indicates the potential risk for the development angle-closure glaucoma because a great range of variation was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Kashiwagi et al reported a close relationship between LCDvh and Shaffer grading systems[25]; (ii) mean ACD for the two Orbscan comparisons. That is, Orbscan versus Smith's technique using a constant of 1.40 (x-axis)(Fig.…”
mentioning
confidence: 98%
“…[21][22][23] Van Herick's peripheral anterior chamber depth assessment was therefore incorporated into the study at this stage, somewhat controversially, in preference to SOG performing gonioscopy, which was excluded. Some studies suggested that Van Herick's technique correlates more closely with occludable angles than direct gonioscopy when compared using high-resolution anterior segment OCT. 16,17 Patients had direct gonioscopy in the HES when judged appropriate by the ophthalmologist. To comply with the new NICE guidelines, we have started training the SOGs on gonioscopy.…”
Section: Discussionmentioning
confidence: 99%